On the night you were born - Tillman, Nancy (New York : Feiwel & Friends, 2006)
The moon, wind, rain, and a variety of animals celebrate the special occasion that is the birth of a child.
First published in the United States in 2005 by Darling Press LLC.
Keywords: Birth -- Fiction; Nature -- Fiction; Stories in rhyme